Analisis Standarisasi Laboratorium Ipa Dalam Mendukung Implementasi Kurikulum Merdeka Di SMP Negeri 3 Kota Langsa - Syaidatul Hadilla; Desi Fitriana; Nurul Mayanti; Monayeno Purba; Nur Azizah Lubis (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
In this research, the Science Laboratory in SMP Negeri 3 Kota Langsa has demonstrated good standardization in supporting the implementation of the independent curriculum. The research findings indicate that the infrastructure support for the science laboratory has an average rating of 87.5% with a classification of very good, while the facility support reaches an average percentage of 90.15% with a classification of very good. The standardization of laboratory personnel has achieved a percentage of 66.66% which falls into the good category, while the standardization of the science laboratory management based on the competencies of the laboratory head has a percentage of 85.16% which is classified as very good. The implementation of the independent curriculum in terms of the principles of learning and assessment is considered good, with a percentage of 72.6%.Overall, the Science Laboratory in SMP Negeri 3 Kota Langsa meets the standards effectively. The laboratory management has adopted a future-oriented approach by implementing digital information technology. Consequently, the Science Laboratory in SMP Negeri 3 Langsa is ready to support the implementation of the independent curriculum.